PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN TEKNIK MIND MAPPING - Desy Maria Damayanti (Universitas Wijaya Kusuma Surabaya, 2020)
This study aims to find varied and effective learning steps to improve poetry writing skills in class VIII B students of SMP Negeri 1 Situbondo by using mind mapping techniques. This research is a classroom action research (PTK). The research subjects were 32 students of class VIII B SMP Negeri 1 Situbondo. The data collection techniques were observation, questionnaires, tests, and documentation. This research was conducted in 2 cycles of action. Based on the results of the pre-action questionnaire, some of the class VIII B students of SMP Negeri 1 Situbondo did not like learning to write poetry. The results of the first cycle research showed that the average result of writing students' poetry using mind mapping techniques was 77.85. Of the 28 students who joined, 18 students scored above the KKM with a percentage of 64.3%. There were 10 students who scored below the KKM with a percentage of 35.7%. At the end of cycle 2, the students' average score was 83.71. Of the 27 students who attended, 24 students scored above the KKM with a percentage of 88.89%. There were 3 students who scored below the KKM with a percentage of 11.11%. From the data processing as a whole, the skills of students in writing poetry have increased. So, it can be concluded that the mind mapping technique is proven to be able to improve the poetry writing skills of VIII B grade students of SMP Negeri 1 Situbondo.